Physical activity & health an interactive approach - Kotecki, Jerome Edward (Jones & Bartlett Learning, 2011)
Physical Activity and Health: An Interactive Approach, Third Edition serves as a valuable text for understanding the workings of the complex systems within the human body and the multidimensional components of human health. This text presents scientific evidence on the relationship between physical activity and health in a readable and understandable format. Filled with information, guidance, recommendations, and practical applications, it prepares students to identify the aspects of personal behavior that, with modification, can improve their overall health. Together with engaging features that address self-assessment and changing health habits, it charts a path that puts students in control and allows them to decide what to do and how and when to do it.